2007
DOI: 10.1021/bi701323k
|View full text |Cite
|
Sign up to set email alerts
|

NMR Analysis of Interaction of LqhαIT Scorpion Toxin with a Peptide Corresponding to the D4/S3−S4 Loop of Insect Para Voltage-Gated Sodium Channel

Abstract: Voltage-gated sodium channels (Navs) are large transmembrane proteins that initiate action potential in electrically excitable cells. This central role in the nervous system has made them a primary target for a large number of neurotoxins. Scorpion alpha-neurotoxins bind to Navs with high affinity and slow their inactivation, causing a prolonged action potential. Despite the similarity in their mode of action and three-dimensional structure, alpha-toxins exhibit great variations in selectivity toward insect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Our analysis identified six new PSSs, in which five (8, 9, 15, 38, and 50) fall into the functional region. The first finding that sites 8 and 9 undergoing positive selection is of particular interest because in Lqh␣IT, these two sites were found to be directly involved in binding to the loop connecting S3-S4 of DIV (abbreviated as L DIV:S3-S4 ) (59) whereas in BmKM1, the residue couplet (8, 9) has been proposed to act as a molecular switch where the substitution at site 8 with specific residue can redirect the ␣-like characteristics of BmKM1 to either insect or much higher specificity to (Fig. 11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis identified six new PSSs, in which five (8, 9, 15, 38, and 50) fall into the functional region. The first finding that sites 8 and 9 undergoing positive selection is of particular interest because in Lqh␣IT, these two sites were found to be directly involved in binding to the loop connecting S3-S4 of DIV (abbreviated as L DIV:S3-S4 ) (59) whereas in BmKM1, the residue couplet (8, 9) has been proposed to act as a molecular switch where the substitution at site 8 with specific residue can redirect the ␣-like characteristics of BmKM1 to either insect or much higher specificity to (Fig. 11).…”
Section: Discussionmentioning
confidence: 99%
“…To observe the locations of these three loops on the channel, we reconstructed a model structure of DmNa v 1, in which L DI:S5-S6 was found to be located between L DIV:S5-S6 and L DIV:S3-S4 , making these three loops form a contiguous region (Fig. 12A and 12B) (59). Of these functional residues, three (8,9, and 18) have been identified here as PSSs, suggesting that this loop constitutes a critical driving force for the adaptive evolution of Mesobuthus ␣-scorpion toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Subtle Alterations at the Bioactive Surface Lead to Marked Differences in Toxin Selectivity-As previously mentioned, a rational approach in the design of a target-selective scorpion toxin first requires that amino acid residues involved in bioac- (21,22,51). Note the division of the bioactive surface in the three toxins to a core domain and an NC domain.…”
Section: Hismentioning
confidence: 99%
“…Recently, Schnur et al (2008) has shown that peptides corresponding in sequence to the extracellular S3-S4 loop in domain 4 of the α-subunit of Na v s (D4/S3-S4), exhibit millimolar affinities for LqhαIT. This provided new insights into receptor site 3 and its toxin binding mechanism.…”
Section: Discussionmentioning
confidence: 99%